2021
DOI: 10.1186/s12873-021-00544-x
|View full text |Cite
|
Sign up to set email alerts
|

suPAR cut-offs for stratification of low, medium, and high-risk acute medical patients in the emergency department

Abstract: Background Soluble urokinase plasminogen activator receptor (suPAR) levels have previously been associated with readmission and mortality in acute medical patients in the ED. However, no specific cut-offs for suPAR have been tested in this population. Methods Prospective observational study of consecutively included acute medical patients. Follow-up of mortality and readmission was carried out for 30- and 90 days stratified into baseline suPAR <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…This is supported by our study, where we found an AUC of 0.72 of procalcitonin on 30-day mortality. suPAR showed the highest AUC on 30-day mortality in our study, which corresponds to other ED studies that investigated the predictive value of suPAR and also report AUCs between 0.80 and 0.84 [10,12].…”
Section: Discussionsupporting
confidence: 88%
“…This is supported by our study, where we found an AUC of 0.72 of procalcitonin on 30-day mortality. suPAR showed the highest AUC on 30-day mortality in our study, which corresponds to other ED studies that investigated the predictive value of suPAR and also report AUCs between 0.80 and 0.84 [10,12].…”
Section: Discussionsupporting
confidence: 88%
“…As a previous study working with the same research data has concluded [ 27 ], this study confirms that suPAR has prognostic value in predicting both negative and positive outcomes: patients with increased suPAR levels are more likely to die within 30 days of index admission, and patients with low suPAR levels are more likely to be discharged from the ED and survive within 30 days of index admission, regardless of age. Vice versa, the suPAR levels among patients who died within 30 days were significantly higher than the levels of the discharged patients.…”
Section: Discussionsupporting
confidence: 84%
“…suPAR has been shown to be a prognostic marker in a wide range of conditions involving an inflammatory state, including sepsis and pneumonia but also myocardial infarction, chronic obstructive pulmonary disease (COPD), chronic kidney disease, diabetes, and cancer [ 19 , 24 30 ] and suPAR is measured routinely in some EDs in Denmark [ 31 ]. Levels < 4.0 have been considered as “low risk” among ED patients and support discharge from the ED [ 32 ], while levels > 6.0 ng/mL have been proposed to indicate a high risk for death [ 32 ]. The current results support that high levels of suPAR are associated with a poor outcome not only among patients with an infection.…”
Section: Discussionmentioning
confidence: 99%